Covidiot di Masyarakat Post-Truth: Dari Anti-Otoritarianisme ke Anti-Religiusitas - Abdullah Muslich Rizal Maulana; M. Kharis Majid; Tonny Ilham Prayogo; Tistigar Sansayto (Jurnal Pemikiran Sosiologi, 2021)
This article aimed to elaborate on 'Covidiot' as discourse emerged within the Post-Truth Society and how it is linked to 'Anti-Authoritarianism' and 'Anti-Religiousity'. It turns out that Covidiot is considered as one of the lethal ignorance practised by the global communities,  refuting parts or the whole COVID-19 protocols regulated by the government while at the same time distributing the massive number of hoaxes. In order to enquire into the discussion, Researcher utilized the 'Discourse-Analysis' method uncovering the ideological substance of Covidiot, starting from its definition and history, followed by an analysis concerning a relationship between COVID-19 and the Post-Truth era. The research continued with a proper comprehension regarding the impact of Covidiot on society and ended with a reflection regarding how Covidiot symbolized an act of 'Anti-Authoritarianism' and 'Anti-Religiousity'. This paper concluded that Covidiot in the Post-Truth society is in urgent demand of the sustained approach from government officers and religious figures to successively educate society further about the jeopardy of Covidiot.